2021
DOI: 10.1002/chem.202004621
|View full text |Cite
|
Sign up to set email alerts
|

As Nice as π: Aromatic Reactions Activated by π‐Coordination to Transition Metals

Abstract: π‐Coordination of aromatic molecules to metals dramatically alters their reactivity. For example, coordinated carbons become more electrophilic and C−H bonds of coordinated rings become more acidic. For many years, this change in reactivity has been used to trigger reactions that would not take place for uncoordinated arenes, however, there has been a recent resurgence in use of this technique, in part due to the development of catalytic reactions in which π‐coordination is transient. In this Minireview, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Aromatic halides are a very important substance class, as they allow a large variety of functional derivatizations, in particular C−C coupling reactions [13] . It could also be shown, that many of these aromatic reactions can be activated by π‐ coordination to transition metals [14,15] . Starting from tetraiodocyclobutadienyliron‐ or pentaiodocyclopentadienylmanganese half‐sandwich complexes star‐shaped polyalkynylated complexes were obtained by Stille coupling reactions [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic halides are a very important substance class, as they allow a large variety of functional derivatizations, in particular C−C coupling reactions [13] . It could also be shown, that many of these aromatic reactions can be activated by π‐ coordination to transition metals [14,15] . Starting from tetraiodocyclobutadienyliron‐ or pentaiodocyclopentadienylmanganese half‐sandwich complexes star‐shaped polyalkynylated complexes were obtained by Stille coupling reactions [16] .…”
Section: Introductionmentioning
confidence: 99%
“…The bonding of unsaturated organic species to transition metals has been known since the pioneering synthesis of [PtCl 3 (C 2 H 4 )] − in 1831 [ A (Figure )]. , The advent of metallocene chemistry is marked by the synthesis of ferrocene ( B ) in 1951, and since these foundational discoveries, the bonding of unsaturated hydrocarbons with transition metals has been extensively studied. Substituting a carbon atom for boron in benzene results in a six-membered anionic species, boratabenzene ( C ), that contains six π-electrons and can be considered a boron-containing hybrid of benzene and cyclopentadienide . Cobalt boratabenzene complex D was disclosed by Herberich in 1970, and these anionic BC 5 heteroarenes have been investigated as ligands for transition metals with complexes having diverse applications, including single-ion magnets as well as olefin polymerization and hydrogenation catalysts. …”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, in the presence of potassium at high temperature (>180 °C), addition reactions of ethylene with an alkylbenzene such as ethylbenzene afford dihydroindenes as minor products via an unusual (3 + 2) cycloaddition; however, the harsh conditions required for this transformation limit its utility. , In previous work, we found that a Rh­(III) catalyst facilitates the deprotonation of benzylic C–H bonds via the electron-withdrawing effect of π-coordination to the aromatic ring, readily generating a nucleophilic benzylic carbanion . Given that metal binding to arenes dramatically affects their charge distribution, we wondered whether we could use π-coordination to alter the reactivity of benzylic carbanions by varying the ligands so that the carbanions would undergo (3 + 2) cycloaddition rather than nucleophilic addition. As an early hint contributed by the Amouri group in 2000, a unique cycloaddition of Ir-complexed o -quinone methide with N -methylmaleimide afforded a zwitterionic complex; however, a similar rhodium complex was demonstrated not to undergo such transformation .…”
mentioning
confidence: 99%